EXPLORING READING INSTRUCTION OF SECONDARY SCHOOLS ENGLISH TEACHERS IN BANDUNG - Muhammad, Hasanul 'Aqil (2018)
This study was aimed at exploring the reading instruction practices as well as the subsequent instructional reading approach of four distinct secondary language teachers in Bandung. The data primarily gained from both classroom observation and stimulated recall interview revealed the intricacy of instruction which made up their respective reading classrooms. The intricacy was sourced by complex combination of several interrelated factors such as the teachers' understanding of reading as a content knowledge, the instructional strategies and also the curriculum relevance. These three factors were taken into consideration to some extent which influenced their instructional reading design and practices. Besides, the teachers also accommodated students' individual differences which signified a contextual factor. Meanwhile, three reading instruction approaches covering transmission-, personal construction- and transaction-oriented instruction have occurred in distinct quality among four teachers. These three instructional reading approaches signified different theoretical learning perspectives that corresponded to the instructional decisions made. The study suggested the teachers to not only be knowledgeable, but also critical and reflective toward the basis aspects relevant to reading instruction in order to promote students' learning.;---Tujuan dari studi ini adalah untuk mengeksplorasi praktik pengajaran membaca dan juga pendekatan pengajaran yang muncul dari empat guru bahasa Inggris SMP-SMA di kota Bandung. Studi kualitatif yang melibatkan dua teknik pengumpulan data berupa observasi kelas dan wawancara stimulated recall interview menemukan kompleksitas instruksi pengajaran yang ada dalam praktik pengajaran di kelas. Kompleksitas tersebut ditimbulkan dari kombinasi berbagai faktor yang saling berkaitan meliputi pemahaman guru terhadap substansi pengajaran reading, strategi-strategi mengajar dan juga relevansinya terhadap kurikulum. Pertimbangan guru terhadap karakteristik individu siswa juga dianggap faktor kontekstual penting. Faktor-faktor tersebut berpengaruh terhadap perencanaan dan praktik mengajar guru. Sementara itu, tiga pendekatan pengajaran membaca yang meliputi pendekatan transmission, personal construction, dan transaction turut muncul dalam berbagai kualitas tertentu pada praktik pengajaran keempat guru. Ketiga pendekatan pengajaran membaca tersebut menunjukan signifikansi spesifik tertentu dalam perspektif pembelajaran dan keputusan pengajaran guru. Studi ini menekankan pentingnya guru untuk tidak hanya memiliki pengetahuan tentang membaca dan pengajarannya yang memadai, tetapi juga kritis dan reflektif dalam upaya mewujudkan pembelajaran pada siswa.